Lack of a bridge between screening and medical management for hypertension: health screening cohort in Japan - Fukuma, Shingo (BMC Public Health, 2020)
BACKGROUND: Patient journeys for hypertensive individuals after detection at screening have not been well examined in a general population. Thus, we aimed to assess the medical treatment status and subsequent longitudinal changes in blood pressure in a middle-aged Japanese population. METHODS: We conducted a cohort study using a nationwide Japanese health screening cohort, from April 2014 to March 2019. Among health screening participants aged 40–74 years who had not previously received treatment for hypertension, hypertensive patients were newly identified based on screening results, and their medical treatment status for hypertension during the year following their initial screening was assessed. The main outcomes were longitudinal changes in systolic blood pressure (SBP) and diastolic blood pressure (DBP) over 4 years after initial screening. RESULTS: Of the 153,523 screening participants (mean age = 49.7 years), 16,720 (10.9%) and 4150 (2.7%) were newly detected as having hypertension, with baseline SBP of 140–159 mmHg (grade 1) and ≥ 160 mmHg (grade 2–3), respectively. Among them, 15.9% of the grade 1 hypertensive participants and 36.3% of the grade 2–3 hypertensive participants started receiving medical treatment during the year following initial screening. A linear generalised estimating equation with propensity score matching showed that receiving medical treatment was associated with 5.77 mmHg lower SBP (95% CI − 6.64 to − 4.90) and 3.82 mmHg lower DBP (95% CI − 4.47 to − 3.16) in the grade 1 hypertensive group, and 14.69 mmHg lower SBP (95% CI − 16.35 to − 13.04) and 8.42 mmHg lower DBP (95% CI − 9.49 to − 7.34) in the grade 2–3 hypertensive group. CONCLUSIONS: Health screenings detected hypertension in a substantial percentage of the middle-aged population in this study. However, detection was often followed by insufficient medical treatment and inappropriate blood pressure management. These findings indicate an inadequate link between health screenings and medical treatments in patients with hypertension.